2019
DOI: 10.31436/iiumej.v20i1.981
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Induced Piezoelectric Energy Harvester via Hybrid Kinetic Motion

Abstract: Piezoelectric energy harvesting is a possible breakthrough to reduce the global issue of electronic waste as they can efficiently convert the ambient vibration to the electrical energy without any additional power. This work presents the design and development of a piezoelectric energy harvester that is capable of transforming vibration from ambient sources into electricity. It focuses on a magnetically plucked piezoelectric beam as an alternative to the mechanically induced harvesters, as the latter are subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Now, these sources are not usually advised due to their unreliability and greenhouse effect on the environment. The development of low-cost PMEH with abundant energy sources could be the future of EH microelectronic devices [165]. Researchers are currently working on improving the efficiency and output power of PMEH.…”
Section: Storing Energymentioning
confidence: 99%
“…Now, these sources are not usually advised due to their unreliability and greenhouse effect on the environment. The development of low-cost PMEH with abundant energy sources could be the future of EH microelectronic devices [165]. Researchers are currently working on improving the efficiency and output power of PMEH.…”
Section: Storing Energymentioning
confidence: 99%
“…Vibration is the embodiment of mechanical energy in an elastic system of some sort continuously changing from mechanical kinetic to potential energy smoothly over and over again. Many conversions of mechanical energy (waste vibration) converted into electrical energy have been done using electromagnetic [8]- [10], piezoelectric [11]- [16], and electrostatic [17]- [20].…”
Section: Introductionmentioning
confidence: 99%
“…Batteries are the single largest source of electronic waste on a global scale. These conventional batteries contain hazardous elements that can be lethal to human health and the environment if not disposed of correctly [2].…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric energy harvesters can have high output voltage from vibration as compared to other conversion mechanisms such as electromagnetic and electrostatic energy harvesters [7]. Additionally, it has been demonstrated that PZT-5H can generate a greater voltage than polyvinylidene difluoride (PVDF), aluminum nitride (AIN), and barium sodium niobate (Ba2NaNb5O15) [2]. Traditionally, the piezoelectric energy harvester is designed as a linear resonator and only works effectively within a narrow bandwidth of frequency.…”
Section: Introductionmentioning
confidence: 99%